Straightforward neuron micropatterning and neuronal network construction on cell-repellent polydimethylsiloxane using microfluidics-guided functionalized Pluronic modification. Issue 2 (4th January 2021) - Liu, Wenming; Fu, Wenzhu; Sun, Meilin; Han, Kai; Hu, Rui; Liu, Dan; Wang, Jinyi
Abstract : We present straightforward neuron patterning and neuronal network construction on polydimethylsiloxane based on functionalized Pluronic modification using microfluidics-guided flow deposition. Abstract : Neuronal cell microengineering involving micropatterning and polydimethylsiloxane (PDMS) microfluidics enables promising advances in microscale neuron control. However, a facile methodology for the precise and effective manipulation of neurons on a cell-repellent PDMS substrate remains challenging. Herein, a simple and straightforward strategy for neuronal cell patterning and neuronal network construction on PDMS based on microfluidics-assisted modification of functionalized Pluronic is described. The cell patterning process simply involves a one-step microfluidic modification and routine in vitro culture. It is demonstrated that multiple types of neuronal cell arrangements with various spatial profiles can be conveniently produced using this patterning tool. The precise control of neuronal cells with high patterning fidelity up to single cell resolution, as well as high adhesion and differentiation, is achieved too. Furthermore, neuronal network construction using the respective cell population and single cell patterning prove to be applicable. This achievement provides a convenient and feasible methodology for engineering neuronal cells on PDMS substrates, which will be useful for applications in many neuron-related microscale analytical research fields, including cell engineering, neurobiology, neuropharmacology, and neuronal sensing.